What drives customers to continue using ride-sharing apps during the COVID-19 pandemic? The case of Uber in Egypt - Hazem Rasheed Gaber; Ahmed Mousa Elsamadicy (Cogent Business & Management, 2021)
The outbreak of the COVID-19 pandemic has caused big changes to customers' perceptions and attitudes towards ride-sharing apps. The purpose of this article is to examine the factors that influence customers' intention to continue using ride-sharing services during the pandemic. A conceptual model was developed based on the unified theory of acceptance and use of technology (UTAUT) and an extensive literature review. An online survey was used to collect data from 398 users of Uber ride-sharing services in Egypt. The partial least squares structural equation modeling (PLS-SEM) was used to test and validate the proposed model. The findings showed that customers' intention to continue using the ride-sharing apps during the pandemic is influenced by four factors which are performance expectancy, economic benefits, facilitating conditions and social influence. It indicated that customers' effort expectancy, perceived infectability and fear of COVID-19 do not affect their intention to use these services. The article contributes by examining the UTAUT in the context of ride-sharing apps during the pandemic. It provides some guidelines for companies that provide ride-sharing services to follow to help them survive with the big challenges they have faced during the pandemic.
Keywords: 650; Uber; sharing economy; ride-sharing apps; COVID-19 pandemic; UTAUT; coronavirus; customer intention